89.7k views
4 votes
Match the order of the step to the steps to solve this equation.

Match the order of the step to the steps to solve this equation.-example-1

1 Answer

4 votes

let the following equation:


(2x)/(3)-6\text{ = 2}

To solve the equation, follow the next steps:

1. MULTIPLY BOTH SIDES BY 3 :


3((2x)/(3)-6)\text{ = 3X2}

this is equivalent to say:


2x-18\text{ = }6

2. DIVIDE BOTH SIDES BY 2 :


(2x-18\text{ ) }(1)/(2)\text{= }(6)/(2)

this is equivalent to say:


x-6\text{= }3

3. ADD 6 TO BOTH SIDES:


x-6+6\text{= }3+6

this is equivalent to say:


x\text{= }3+6\text{ = 9}

Match the order of the step to the steps to solve this equation.-example-1
User Elahe
by
4.9k points